Efek Dolomit Dan Sp-36 Terhadap Bintil Akar, Serapan N Dan Hasil Kacang Tanah (Arachis hypogaea L.) Pada Tanah Kambisol - Charles Silahooy (Faculty of Agriculture, Pattimura University, 2012)
Maluku in general and Ambon municipality in particular is a region with the lowest peanut production as compared to its national production. Cambisol is one of soil type that has good soil physical properties, but it is low in N and P contents and has an acidic reaction that inhibit the growth of peanut plants. The research was conducted in a plastic house in Halong Village, Teluk Ambon Baguala Subdistrict, from April to Juli 2012. This research used a Completely Randomized Design with two factors, i.e. factor 1 with three levels of dolomite fertilization, consisting of D0 (without dolomite), D1 (0.3g dolomite per pot), D2 (0.6 g dolomite per pot), and factor 2 with three levels of phosphate fertilization consisting of P0 (without phosphate fertilizer), P1 (0.7 g SP-36 per pot) and P2 (1.4 SP-36 per pot). The results showed that the application of SP-36 increased the number of root nodules and yield of peanut. Response was even better if accompanied by the application of dolomite. Leaf N uptake could be enhanced by application SP-36, but it was independ from the application of dolomite. The highest peanut yield of 41.83 g per pot was achieved with the fertilizer combination of D1P2 (0.3 g dolomite per pot and 1.4 g SP36 per pot)